Effects of herbal acupuncture(Atratylodes japonica, Coix lachrymajobi, Ephedra sinica, Atratylodes japonica mixed with Coix lachrymajobi and Ephedra sinica mixed with Green tea) at Pungnyung(ST40) and Umnungchon(SP9) in obese Rats induced by high fat diet - Dae-Hwan Youn; Ja-Don Kang; Joon-Sung Joo; Woo-Seok Chae; Chang-Su Na (Korean Pharmacopuncture Institute, 2004)
Objectives : This research was performed to investigate the effect of herbal acupuncture (Atratylodes japonica, Coix lachrymajobi, Ephedra sinica, Atratylodes japonica mixed with Coix lachrymajobi and Ephedra sinica mixed with Green tea) at Pungnyung(ST40) and Umnungchon(SP9) on weight gain, food intake, food efficiency, serum of lipid concentrations, liver function and HDL to total cholesterol ratio of rats fed high fat diet for 5weeks. Methods : Experimental groups were divided into normal group(Normal), high fat diet group(Control), high fat diet and Atractylodes japonica-herbal acupuncture group (AJ), high fat diet and Coix lachrymajobi-herbal acupuncture group(CL), high fat diet and Ephedra sinica-herbal acupuncture group (ES), high fat diet and Atractylodes japonica+Coix lachrymajobi-herbal acupuncture group(AJ+CL), Ephedra sinica+Green tea-herbal acupuncture group(ES+GT). Herbal acupuncture was bilaterally treated at the level of 132.5mg/kg body weight per 2day. Results : Body weight and food efficiency were decreased in AJ, ES, AJ+CL, ES+GT. The level of serum total cholesterol, triglyceride and free fatty acid were increased in AJ, ES, ES+GT. That of serum HDL-cholesterol was increased in AJ. The change of food intake, the level of serum phospholipid and ALP were not significant. The HDL to Total cholesterol ratio was increased in AJ and ES. Conclusions : Atractylodes japonica-herbal acupuncture in ST40·SP9 is effective on Body weight, food efficiency ratio, the level of serum lipid, protection of liver function and prevention cardiovascular risk by obesity induced by high fat diet. Herbal acupuncture mixed Ephedra sinica with Green tea can control the body weight, food efficiency ratio and the level of serum lipid.